Development of buckboost converter for DC motor speed control application - Ahmad Efendi, Mohamad (2010)
In the current century, DC motors plays a vital role in industrial areas. The efficient motor, are motor that be able to control the speed. Motor speed is controller by signal representing from microcontroller, in this project, the power converter for DC motor application is developed. One type of common method is by using Pulse Width Modulation (PWM), to control the speed of DC motor. Rectifiers which converted AC to DC supply and buck/boost converter are used to step up/step down a voltage or current while DC motor used as a load. Supplies to the DC motor are developed and the output is controlled by using PWM. PIC microcontroller is used to generate the PWM wave which can be varied in duty ratio, in order to create another level of DC voltage. This project starts with design circuit of a buck-boost converter using Orcad software and also Proteus 7.6 professional. In addition, hardware prototype has been developed based on the circuit designed. The system performance are evaluated and analyzed in comparison with a simulation results, at the end of this project the motor speed will satisfied the desired speed.